CYP4BN4v7 regulates the population density dependent oocyte maturity rate in bean beetles - Qianquan Chen; Yongqin Li; Zheng Fang; Qingshan Wu; Leitao Tan; Qingbei Weng (Scientific Reports)
Abstract The bean beetle (Callosobruchus maculatus) clearly exhibits population density-dependent polymorphism. Cytochrome P450 (CYP) is involved in many aspects of the physiological activities of insects. However, the role of CYP in population density-dependent polymorphisms remains unknown. The terminal oocyte maturity rate of high-population-density individuals (H) was faster than that of low-population-density individuals (L). A total of 56 CYP-like genes were identified from transcriptomic and genomic data, including seven clan 2 CYP-like genes, seven mitochondrial CYP-like genes, 19 clan 3 CYP-like genes, and 23 clan 4 CYP-like genes. Gene duplication might occur in CYP9Z4-like, CYP345A1-like, CYP345A2-like, CYP349A1-like, CYP349A2-like, and CYP4BN4-like. Thirteen and two CYP-like genes were up-regulated and down-regulated, respectively, in H. Among these CYP-like genes, CYP4BN4v7-like was the most abundant CYP. CYP4BN4v7-like was more highly expressed in the head than in the thorax and abdomen. Its mRNA levels in the head, thorax, and abdomen were greater in H than in L. After RNA interference decreased its mRNA level, the terminal oocyte maturity rate decreased. Moreover, the expression level of insulin-like peptide 1 (ILP1), which plays a vital role in regulating terminal oocyte development, decreased in the head. In conclusion, CYP4BN4v7-like modulated the population density-dependent terminal oocyte maturity rate by regulating the expression of ILP1.